Levels of feed supplementation on the qualitative aspects of meat from crossbred goats finished on caatinga (Revista Ciência Agronômica, 2015)
The effect was evaluated of feed supplementation (0.0, 0.4, 0.8, and 1.2% of body weight) on the qualitativeaspects of goat meat (moisture, ash, fat, protein, colouring using the CIE (L*, a* and b *) system, pH, cooking loss andshear force), and also on the sensory attributes of goat aroma, off-aroma, colour, texture, tenderness, flavour, off-flavour,juiciness and overall appearance. A total of 32 crossbred Anglo-Nubian goats were used, organised into randomised blocksand finished on a pasture of caatinga. There was a quadratic effect (p